Society and development : - Surjit Singh; Raina, Dhruv (Rawat Publications, 2016)
The notion of the region and its significance in contemporary societies is much debated and contested. Visible uneven development and rising inequalities have forced social scientists, analysts and policy makers to rethink development in a regional perspective. This collection of select papers presented at the First Northern Regional Social Science Congress held in 2013 in Jaipur offers a regional perspective on Society and Development. The papers address a wide range of developmental problems of the Northern Region in the social sciences from an interdisciplinary perspective. The volume is illustrated with a wide range of case studies with themes ranging from the problem of inclusion of minorities, changing village economy, gender and health, labour and migration, issues of governance, as well as urbanization seen through different disciplinary lenses. The contributors include some distinguished social scientists, as well as a significant member of young social scientists embarking on their research careers. The volume will certainly mark the recognition of the serious scholarly engagement in social science research at the regional level. The varied, yet interlinked, nature of issues covered in this book will be a valuable resource for academics, researchers, policy makers and development practitioners.